My Hero Academia. Vol. 10, All for one - Horikoshi, Kōhei, 1986-; Cook, Caleb D. (Shonen Jump manga., 2017)
After Bakugo is abducted by the League of Villans, there is an uproar and the Hero Academy's faculty works to reverse public opinion while the students of Class 1-A plot a rescue mission.